ASPEK SUBCONSCIOUS MIND DALAM TERM-TERM UTAMA PENDIDIKAN AGAMA ISLAM - Ahmad, Victor Imaduddin (Akademika, 2017)
The purpose of this study is to find the subsconcious aspects in the main terms of Islamic education and what the urgency of the study is. first and foremost in Islamic Education is Faith, faith lies in the heart, and the substance of the heart is a representation of the system of mind in which the greatest part is the subconscious or subconscious mind. the second is Islam with its five pillars, all of which are the extension of the hand or representation of the faith in the form of vertical and horizontal ritual worship ritual, and then the third term which is the purpose of the dispensation of the Prophet Muhammad SAW is the term morality. Akhlaq noble essence is a representation that one's subconcious condition has been well structured by religious guidance ranging from beliefs, self-image, emotion, character to the habit of doing. From the study it is found that the dominant subsconcious aspect is found in the terms of Islamic Education, and the urgency to understand the subsconscious aspect is that subsconcious affects the human life of 88%, hence to consecrate one's religious building, not enough to organize the conscious but also the subconcious in a way understand the characteristics and how it works.Keywords: Subconcious, Main Term, Islamic Religious Education